Intrinsic Factors Contributing to Shrimp and Blood Clamp Allergic Reaction and Allergic Like Symptoms - Azzahra, Almasah; Kausara, Bramanti Nadya; Abdi Sahid, Muhammad Novrizal (Journal of Food and Pharmaceutical Sciences, 2023)
Factors that contribute to food allergenicity is still unknown. To determine food intrinsic properties that contribute to L. vannamei and A. granosa allergenicity or allergy like symptoms this study identify total protein and metal profiles, histamine contents, and protein heat stability. Histamine content is measured colorimetrically. Protein heat-stability is observed with sodium dodecyl sulfate – polyacrylamide gel electrophoresis (SDS-PAGE). Allergy-related metal concentration are determined with Atomic Absorption Spectroscopy (AAS). Fresh L. vannamei and A. granosa contained ~100 and ~25 ppm histamine, respectively. Storage at -20 oC for 3 days relatively did not changed histamine content of both foods. Storage at 4-8 oC for 3 days increased histamine content in L. vannamei, but not in A. granosa. Protein sized <70 kDa of both samples are relatively heat-stable. L. vannamei and A. granosa contained Zn with concentration of 85 ppm and 92 ppm, subsequently. All samples did not contain nickel (Ni), chromium (Cr), and lead (Pb). Higher histamine content and heat-stable protein number of L. vannamei could contribute to higher prevalence of its allergy or allergic like symptoms than A. granosa. High Zn content might contribute to allergic like symptoms of both foods.